Pengaruh Earning Per Share (EPS), Return On Equity (ROE), Dan Net Profit Margin (NPM) Terhadap Harga Saham: Studi Pada Perusahaan dalam Indeks LQ45 periode Agustus 2018 hingga Januari 2019 - Zalukhu, Rika Surianto; Hutauruk, Rapat Piter Sony; Colyn, Daniel; Sudarjah, Gugum Mukdas (Accounting Progress, 2023)
The purpose of this study is to analyze the effect of earnings per share (EPS), return on equity (ROE), and net profit margin (NPM) on stock prices. The dependent variable of the study is the stock price while the independent variables of the study are EPS, ROE and NPM. The study was conducted on LQ45 index companies listed on the Indonesia Stock Exchange (IDX) for the period from August 2018 to January 2019. The study population consisted of 45 companies, and the sampling technique used was saturated sampling. This study uses secondary data. The data was analyzed using multiple linear regression analysis methods. The results of the analysis show that earnings per share and return on equity have a partially positive and significant effect on stock prices. While Net Profit Margin has a negative and insignificant effect on stock prices. Earning per share, return on equity and net profit margin simultaneously have a significant effect on stock prices.